Une métaphore de la démarche géographique et de l’histoire du XIXe siècle : L’Île Mystérieuse de Jules Verne (1874-75) - Lionel Dupuy (Cybergeo, 2011)
Carrying on the analysis conducted by Jean-Louis Tissier in 1996, in which he considers Mysterious Island (1874-75) of Jules Verne as a parable of the geographical approach, this article shows how this novel could also be read as a metaphor of XIXth century history.